Pengaruh Pendampingan Belajar Orang Tua Terhadap Hasil Belajar PAK-BP Pada Siswa Kelas VII SMP Katolik Gonzaga Tomohon - Hadi Ignatius Untu; Asri Rumagit (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
Parents as educators first and foremost, in fact, do not carry out their responsibilities in accompanying children to learn at home. Lack of learning assistance has a negative influence on children so that their learning outcomes are less satisfactory. Such problems were also found in grade VII students of Gonzaga Tomohon Catholic Junior High School which prompted researchers to raise a study entitled "The Effect of Parental Learning Assistance on PAK-BP Learning Outcomes in Grade VII Students of Gonzaga Catholic Junior High School". This study aims to determine parental learning assistance, how student PAK-BP learning outcomes and how much influence parental learning assistance has on PAK-BP learning outcomes in grade VII students of Gonzaga Tomohon Catholic Junior High School. The quantitative approach method is a research method that researchers use. This study used independent variable X (parental learning assistance) and dependent variable Y (student PAK-BP learning outcomes). The sample amounted to 93 respondents randomly drawn from a population of 121 students. Problem formulations 1, 2 are answered using descriptive analysis while problem 3 formulations are answered using simple linear regression analysis. The results showed that parental learning assistance was in the very good category with a value of 0.856. PAK-BP learning outcomes are in the very high category with a value of 0.851. There is also a low and significant influence of parental learning assistance on PAK-BP learning outcomes in grade VII students at Gonzaga Tomohon Catholic Junior High School with a coefficient of determination of 0.371 equivalent to 37% and 63% are other influencing factors.